2019
DOI: 10.1021/jacs.8b12935
|View full text |Cite
|
Sign up to set email alerts
|

Unified Mechanism of Oxygen Atom Transfer and Hydrogen Atom Transfer Reactions with a Triflic Acid-Bound Nonheme Manganese(IV)–Oxo Complex via Outer-Sphere Electron Transfer

Abstract: Outer-sphere electron transfer from styrene, thioanisole, and toluene derivatives to a triflic acid (HOTf)-bound nonheme Mn­(IV)–oxo complex, [(N4Py)­MnIV(O)]2+–(HOTf)2 (N4Py = N,N-bis­(2-pyridylmethyl)-N-bis­(2-pyridyl)­methylamine), has been shown to be the rate-determining step of different types of redox reactions such as epoxidation, sulfoxidation, and hydroxylation of styrene, thioanisole, and toluene derivatives, respectively, by [(N4Py)­MnIV(O)]2+–(HOTf)2. The rate constants of HOTf-promoted epoxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 120 publications
4
27
0
Order By: Relevance
“…We took inspiration from the well-studied reactivities in homogeneous catalytic oxidation and utilized typical reactivities of oxygen atom transfer (OAT) and hydrogen atom transfer (HAT). OAT probes, often including phosphines, thioethers, and alkenes, can specifically target oxygen-terminated structures for abstracting oxygen atoms. HAT probes, often C–H-based molecules, can specifically target oxygen-associated high-valent metal species, such as metal oxo and metal peroxo species, for donating H atoms to generate the corresponding radical. , These reactivities can widely exist on the oxygen intermediates formed during OER and we anticipate that probes with different reactivity can behave divergently, allowing for the differentiation and identification of oxygen intermediates. To be compatible with in situ experiments, the reactive probes should also demonstrate high solubility and chemical stability in the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took inspiration from the well-studied reactivities in homogeneous catalytic oxidation and utilized typical reactivities of oxygen atom transfer (OAT) and hydrogen atom transfer (HAT). OAT probes, often including phosphines, thioethers, and alkenes, can specifically target oxygen-terminated structures for abstracting oxygen atoms. HAT probes, often C–H-based molecules, can specifically target oxygen-associated high-valent metal species, such as metal oxo and metal peroxo species, for donating H atoms to generate the corresponding radical. , These reactivities can widely exist on the oxygen intermediates formed during OER and we anticipate that probes with different reactivity can behave divergently, allowing for the differentiation and identification of oxygen intermediates. To be compatible with in situ experiments, the reactive probes should also demonstrate high solubility and chemical stability in the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…We took inspiration from the well-studied reactivities in homogeneous catalytic oxidation and utilized typical reactions of oxygen atom transfer (OAT) and hydrogen atom transfer (HAT). OAT probes can specifically target oxygen-terminated structures for abstracting oxygen atoms, often including phosphines, thioethers and alkenes [33][34][35] . HAT probes, often C-H-based molecules, can specifically target oxygen-associated high-valent metal species, such as metal oxo and metal peroxo species, for donating H atoms to generate the corresponding radical [36][37] .…”
Section: Designing and Screening Of Reactive Probesmentioning
confidence: 99%
“…Protons are known to play important roles in tuning redox potentials and reactivities of metalloenzymes and metal catalysts in oxidation reactions, such as in water oxidation, substrate oxidation, dioxygen reduction, and proton reduction. , In this context, Brønsted acids, such as perchloric acid (HClO 4 ) and triflic acid (HOTf), and Lewis acids, including redox-inactive metal ions, have been shown to enhance the electron transfer (ET) and oxidizing capability of high-valent nonheme metal­(IV)–oxo complexes via a proton-coupled electron-transfer (PCET) mechanism. For example, binding of a redox-inactive metal ion (e.g., Sc 3+ ion) to the oxo ligand of a nonheme iron­(IV)–oxo complex has shown dramatic enhancement of the rates of ET reactions. , In addition, binding of Lewis acidic metal ions or triflic acid to the oxo moiety of nonheme Mn­(IV)–oxo complexes resulted in the large acceleration of rates of ET and OAT reactions. It was also shown that the Brønsted and Lewis acids increased the catalytic reactivity of metal catalysts in oxidation reactions. In heme models, Karlin and co-workers reported an elegant result demonstrating that the binding of 2,6-lutidinium triflate to an iron­(IV)–oxo porphyrin complex via hydrogen bonding resulted in a significant enhancement of the oxidizing capability of the iron­(IV)–oxo porphyrin complex along with a positive shift of the one-electron reduction potential by >0.89 V. , In the case of a Mn­(V)–oxo TAML complex, a Lewis acidic metal ion (e.g., Sc 3+ ion) was shown to bind to the TAML ligand, which resulted in an enhancement of the oxidizing power of the Mn­(V)–oxo complex with a positive shift (0.70 V) of the one-electron reduction potential . However, to the best of our knowledge, the effects of proton and metal ion on the chemical properties of nonheme iron­(V)–oxo complexes have never been explored previously.…”
Section: Introductionmentioning
confidence: 99%
“…The LMCT energy of [(Bn‐TPEN)Mn IV (O)] 2+ ([(Bn‐TPEN .+ )Mn III (O)] 2+ ) is expected to decrease by increasing the number of binding molecules of Sc(OTf) 3 from one to two, because the electron accepting ability of the Mn IV (O) moiety increases with an increase in the number of binding molecules of Sc(OTf) 3 from one to two. The λ value of 0.53 eV is much smaller than that of the ground state of Mn IV (O) complexes ( λ =2.2–2.3 eV) [12,29] because of the ligand centered electron transfer to the ligand‐to‐metal charge transfer (LMCT) excited state of [(Bn‐TPEN)Mn IV (O)] 2+ −Sc(NO 3 ) 3 as compared with the metal‐centered electron transfer to the ground state of Mn IV (O) complexes. Sc(NO 3 ) 3 is known to act as a strong Lewis acid even in an aqueous solution [30,31] …”
Section: Resultsmentioning
confidence: 98%